Meningkatkan Motivasi Belajar Siswa Sekolah Dasar Dalam Pelajaran Pkn Melalui Model Pembelajaran Kooperatif Tipe Team Game Tournament - Devy, Afriza Anggita (Prosiding University Research Colloquium, 2021)
The purpose of this study was to increase students' learning motivation in Pancasila subject matter PKN lessons by using the Cooperative Model Type Team Game Tournament. The research method used is Classroom Action Assessment (CAR) which consists of 3 cycles and each cycle consists of stages of planning, action, observation and reflection activities. Based on the implementation of the Team Game Tournamnet Model, to increase students' learning motivation, students get learning outcomes, namely Cycle I with an average of 59.4 because students are still not familiar with the TGT Model. The increase in the acquisition of learning outcomes occurs in Cycle II with an average of 68.6 because students have started interested in the TGT Model and enthusiastic about participating in learning, In Cycle III there was a significant increase with evidence of obtaining learning outcomes with an average of 88.7 because students were used to the fun TGT Model and significantly increased learning motivation. So it can be said that the application of the Team Game Tournament Model in PKN lessons on Pancasila material can increase student motivation and enthusiasm.